2017
DOI: 10.3168/jds.2017-13116
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment records and inventory of empty drug containers to quantify antimicrobial usage in dairy herds

Abstract: Assessment of antimicrobial use (AMU) is vital for interpreting the origin of changes in antimicrobial resistance (AMR). The objectives of the present study were to estimate the association between AMU determined using on-farm treatment records (TR) and inventory of empty drug containers (INV). Herds were selected to represent Canadian dairy farms. Producers were asked to record animal health events and treatments on a standard General Health Event form. For inventory data, 40-L receptacles were placed at vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Thirteen studies reported dose-based data from dairy farms. All studies came from Europe, except one each from Argentina [ 93 ], the USA [ 91 ], and Canada [ 85 ]. One study reported AMU in heifers before calving [ 69 ], and another one reported AMU to treat mastitis [ 91 ] exclusively.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported dose-based data from dairy farms. All studies came from Europe, except one each from Argentina [ 93 ], the USA [ 91 ], and Canada [ 85 ]. One study reported AMU in heifers before calving [ 69 ], and another one reported AMU to treat mastitis [ 91 ] exclusively.…”
Section: Resultsmentioning
confidence: 99%
“…Non- aureus staphylococci (NAS) have emerged as the most frequently isolated group of pathogens in intramammary infections (IMI) in dairy cows, with an estimated udder quarter-level prevalence of 26 cases per 100 quarters (Condas et al, 2017 ). Worldwide, mastitis remains one of the most frequent reasons for antimicrobial therapy in dairy herds (Mitchell et al, 1998 ; Brunton et al, 2012 ; Nobrega et al, 2017 ). Therefore, NAS are in relatively frequent contact with antimicrobials.…”
Section: Introductionmentioning
confidence: 99%
“…Cow mastitis is a detrimental factor in milk quality and food safety (Cha et al, ). The current approach for the drug treatment of cow mastitis is prone to result in residual drugs remaining and drug resistance problems (Nobrega et al, ). In‐depth study of the pathogenic and immune mechanisms of pathogens can provide a theoretical basis for the development of new methods for the treatment and prevention of mastitis.…”
Section: Introductionmentioning
confidence: 99%